Colaboração como fonte de vantagem competitiva em cadeias de suprimentos: análise em empresas do setor de geração Termelétrica - Machado, Tiago Silveira (2016)
In the last years companies have tried mechanisms for the development of competitive advantage and collaboration have been adopted as an alternative for obtaining such advantages. Thus, seeking to contribute to the literature, this research adopted as theoretical lens the Relational View in association with other theories, to analyze how the collaboration between companies operating in a Supply Chain of the thermoelectric sector contributes to the development of competitive advantages. Methodologically, this research developed a systematic review of the literature with the aim of identify factors of competitive collaboration and advantages interorganizational in supply chains, from there, it was elaborated an analysis model. The model was applied in a single case study with multiple units analysis. They were analyzed four companies, one Focal Firm and three suppliers, two of the first layer and second layer. The main instrument of data collection was a semi-structured interview applied with the managers of organizations. Data were analyzed with the Atlas.ti software. Through research it was found that adaptation, commitment, trust and strategic alignment are collaborative factors that are contributing to the development of advantages. Addition to these, communication and conflict resolution emerge as sub-factors that influence both in factors of collaboration such as the competitive advantage. The major sources of competitive advantage in the studied relationships were developing knowledge, exchange and sharing of knowledge routines, governance mechanisms and shared resources. This is because the members in the relationships believe that it was not necessary to develop specific assets for relationship. The perceived benefits from the collaboration in the supply chain are linked to the financial aspect, improving the efficiency of processes, decrease errors and problems with communication. Analysis of the results, along with the theory studied allowed the development seven propositions that represent the collaboration and interorganizational competitive advantage in the relationships studied.